2016
DOI: 10.4103/1463-1741.189244
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of hyperacusis in the general population

Abstract: There is a need for better understanding of various characteristics in hyperacusis in the general population. The objectives of the present study were to investigate individuals in the general population with hyperacusis regarding demographics, lifestyle, perceived general health and hearing ability, hyperacusis-specific characteristics and behavior, and comorbidity. Using data from a large-scale population-based questionnaire study, we investigated individuals with physician-diagnosed (n=66) and self-reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
76
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 33 publications
11
76
0
4
Order By: Relevance
“…The incidence of caseness was 26% for the PHQ-9, which assesses depression. This 481 value is within the incidence range for depression of 10% (Bartels et al, 2008) to 69% 482 (Andersson et al, 2004) reported for patients whose primary complaint was tinnitus, and 483 slightly above the incidence of depression of 17% reported for patients whose primary 484 complaint was hyperacusis (Paulin et al, 2016). Seventy percent of our patients thought that 485 the PHQ-9 was relevant to them, and 79% recommended it for general use in assessing 486 patients with tinnitus and/or hyperacusis.…”
mentioning
confidence: 49%
See 1 more Smart Citation
“…The incidence of caseness was 26% for the PHQ-9, which assesses depression. This 481 value is within the incidence range for depression of 10% (Bartels et al, 2008) to 69% 482 (Andersson et al, 2004) reported for patients whose primary complaint was tinnitus, and 483 slightly above the incidence of depression of 17% reported for patients whose primary 484 complaint was hyperacusis (Paulin et al, 2016). Seventy percent of our patients thought that 485 the PHQ-9 was relevant to them, and 79% recommended it for general use in assessing 486 patients with tinnitus and/or hyperacusis.…”
mentioning
confidence: 49%
“…Schecklmann et al (2014) reported that 20% of patients with hyperacusis 84 combined with tinnitus were receiving psychiatric care. Paulin et al (2016) reported that 85 among 30 patients with self-reported hyperacusis, 5% had generalised anxiety disorder, 17% 86 had depression and 3.5% had panic disorder. 87…”
Section: Hadsmentioning
confidence: 99%
“…VVC regulation of the middle ear muscles may influence the salience of high and low frequency sounds (evolutionary cues of conspecific distress and predator calls, respectively), maintaining autonomic threat responses via perpetuation of threat-type signals at the cost of frequencies signaling safety (Kolacz, Lewis, & Porges, 2018;Porges & Lewis, 2010). There is increasing evidence that auditory hypersensitivities are elevated in PTSD, anxiety, and depression (Beutel et al, 2016;Jüris, Andersson, Larsen, & Ekselius, 2013;Paulin, Andersson, & Nordin, 2016). Additional studies are needed to understand the link between auditory hypersensitivities and psychosocial problems.…”
Section: Emerg Ing E Viden Ce For De Velopmental Pathwaysmentioning
confidence: 99%
“…So too are several types of muscle tremors and fasciculation. Heightened sensory inputs can manifest as various pain syndromes [26], multiple chemical sensitivity [27], adverse reactions to electromagnetic fields [28], photophobia [29], hyperacusis [30], pruritus [31], paresthesia [32], etc. Inappropriate nerve impulses emanating from damaged neurons can adversely trigger the autonomic nervous system [33]; cause bowel [34] and bladder [35] irritability.…”
Section: Hyperactivity Of the Damaged Brain: Is It A Lowered Thresholmentioning
confidence: 99%